CHE Principles: facilitating authentic and dialogical semi-structured interviews in educational research - Brown, Alice; Danaher, Patrick A. (International journal of research & method in education, 2019)
This paper examines the values of the CHE principles of Connectivity, Humanness and Empathy as a guiding framework for maximizing the ethical and methodological advantages of semi-structured interview research practices. The authors draw from two separate educational studies and apply the CHE principles to analyse and evaluate the effectiveness of decision-making in facilitating sustainable relationships with the participants in each study. Findings highlight that dialogical relations with participants were evident in both studies, and identify significant junctures where decision-making and actions influenced effective rapport-building and respectful and reciprocal relationships with participants in the research. The CHE principles emerge as providing a robust framework for educational researchers to employ when auditing their decision-making prior to and during their engagement in qualitative interviews.